The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1590/s0100-879x1997000300015
|View full text |Cite
|
Sign up to set email alerts
|

Association between polyclonal B cell activation and the presence of autoantibodies in mice infected with Yersinia enterocolitica O:3

Abstract: Eight-week old conventional female Swiss mice were inoculated intravenously with Yersinia enterocolitica O:3. A second group of normal mice was used as control. Five mice from each group were bled by heart puncture and their spleens were removed for spleen cell collection on the 3rd, 5th, 7th, 10th, 14th and 21st day after infection. Immunoglobulin-secreting spleen cells were detected by the isotypespecific protein A plaque assay. Total immunoglobulin levels were determined in mouse serum by single radial immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…The production of autoantibodies may result from polyclonal B lymphocyte activation. We have shown that this association does occur in mice infected with Y. enterocolitica O:3 (22).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The production of autoantibodies may result from polyclonal B lymphocyte activation. We have shown that this association does occur in mice infected with Y. enterocolitica O:3 (22).…”
Section: Discussionmentioning
confidence: 69%
“…We have previously demonstrated that conventional Swiss mice infected with the same strain of Y. entero- colitica developed polyclonal activation of B lymphocytes. This activation was not limited to certain isotypes of immunoglobulins since the number of secretory cells of all isotypes was increased, but IgG 2a -secreting cells did increase more strongly, compared to controls (23).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Polyclonal activation of B lymphocytes in Swiss mice infected with a low-pathogenicity strain, Y. enterocolitica O:3, was first demonstrated in our laboratory (29). Furthermore, Crespo et al (7) demonstrated that Y. enterocolitica O:3 derivatives, such as LPS and Yops, induce polyclonal activation of B lymphocytes.…”
mentioning
confidence: 92%